2003
DOI: 10.1128/jcm.41.11.5240-5244.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hepatitis C Virus Genotyping by 5′ Noncoding Region- and Core-Based Reverse Transcriptase PCR Assay with Sequencing and Use of the Assay for Determining Subtype Distribution in India

Abstract: Phylogenetic analysis of the sequences of the 5 noncoding regions (5NCR) of 149 samples from hepatitis C virus (HCV) RNA-positive chronic carriers representing northern, southern, eastern, and western India showed that type 3 and type 1 are the predominant genotypes circulating in India, with an overall prevalence of 53.69 and 38.25%, respectively. Type 4 viruses (6.04%) were seen only in southern India. Sequence analysis of the core region of 51 of the above isolates enabled us to classify them further into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 35 publications
6
65
0
Order By: Relevance
“…In view of these findings, it is quite apparent that the patients infected with HCV infection in this area of north India come under the category of responding well to antiviral treatment. Our findings are in support of few other studies reported from this country [11,12].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In view of these findings, it is quite apparent that the patients infected with HCV infection in this area of north India come under the category of responding well to antiviral treatment. Our findings are in support of few other studies reported from this country [11,12].…”
Section: Discussionsupporting
confidence: 83%
“…In all these assays the 5'NCR has been frequently used for amplification followed by digestion by different sets of restriction enzymes to detect different subtypes. However, like in other assay systems it is not possible to detect all subtypes by using 5'NCR [12]. Attempts have been made to include the conserved part of other subgenomic regions also both in PCR-RFLP as well as Real Time PCR [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core region was amplified by nested PCR as previous reported (Lole et al, 2003). Briefly, total 50μl of outer reaction mixture include of 5μl cDNA, 5μl of 10X PCR buffer, 125mmole of MgCl2 , 10mmole of dNTPs, 2.5U of Taq pol and 10µmole of each CC1 outer sense primer 5'-ACTGCCTGATAGGGTGCTTGC-3', CC2 outer antisense primer 5'-ATGTACCCCATGAGGTCGGC-3'.…”
Section: Hcv Genome Amplificationmentioning
confidence: 99%
“…In India, Lole et al [12] showed that the infection with type 3 was predominant in North, West and East Indian population, while genotype 1 was shown to be the predominant genotype in South India. The study by Hissar et al [8] also confirmed the predominance of genotype 3 in North and Central India.…”
mentioning
confidence: 99%